The Impact of Television on Academic Performance of University Students: A Case of Ucu School of Journalism, Media and Communication - Charity James Kide (My University, 2024)
This research investigates the impact of television on the academic performance of university student. A case of the school of journalism, media and communication, an area of increasing relevance in the digital age where media consumption patterns are rapidly evolving. The study was guided by the research objectives which; examine the role of television in shaping media literacy, analyze how Television viewing influences the development of journalism skills, explore the television viewing habits of journalism students. The theoretical framework used was the uses and gratification theory. This theory was relevant for the study because it will explore the motivations and gratifications university students derive from television viewing and understand how these factors relate to their academic performance. The study employed an in-depth interview guide as a method of data collection. The findings indicate a nuanced relationship between television viewing habits and academic outcomes, revealing the moderate consumption of educational programming can enhance students’ knowledge and critical thinking skills. Recommendations are provided to foster a balanced approached.